Clinical data analysis of nine years of experience with twin pregnancy: a tertiary hospital-based retrospective study - Yuan Ting; Zhang Ting; Wang Yan-Yan; Li Xue-Lan; Han Zhen (IMR Press, 2022)
Background: The incidence of twin pregnancy has been increasing worldwide and in China. This study provided a comprehensive analysis of the clinical data of twins in a Chinese tertiary hospital and summarized the clinical characteristics. Methods: A retrospective collection of data was carried out for 717 cases of twins in the Obstetrics Department of the First Affiliated Hospital of Xi'an Jiaotong University from 2011 to 2020. A comprehensive analysis of baseline information and maternal and perinatal outcomes was conducted, and the twin birth rate of the study population was also calculated. Results: The average twin delivery rate was 2.61%. A total of 206 cases were monochorionic, and 511 cases were dichorionic. Premature delivery, hypertensive disorder complicating pregnancy and premature rupture of membranes were the three most common complications. Caesarean section rates from 2011 to 2019 were maintained at 70%-80%. A total of 144 cases (20.08%) of 717 twin cases were complicated twins. Birthweight discordance ≥25% accounted for 13.53% of cases. Adverse neonatal outcomes with higher incidences were neonatal respiratory distress syndrome, small for gestational age and 1 min Apgar score ≤7. Conclusions: Twin pregnancy has different and unique clinical features. Obstetricians should pay close attention to its clinical management to obtain better perinatal outcomes.